DOVETAILING CULTURAL VALUES TO ENGLISH LANGUAGE TEACHING - Lalitha Ramamurthi (Soegijapranata Catholic University, 2005)
One of the aftermaths of colonial rule in India has been the legacy of English language and literature. Even in this postcolonial phase of renewed interest in national literature, English continues to be the lingua franca in this multi-lingual and multi-racial nation. Yet, this paper argues, there is perceptible change sweeping the English curriculum in Indian universities. The change in the content of ELT has been effected with a view to introduce Indian cultural values in the place of heavy alien western content. The General English course which is common to all the undergraduate students now includes value-based culture-centered essays and speeches by Indian cultural exponents like Vivekananda, Dr. Radhakrishnan, Mahatma Gandhi, Rabindranath Tagore and Nehru .The English major paper, too includes works of well- known Indian English writers and translations of regional writings. The paper addresses the continued need for English in the national and international arena, but demonstrates that the content of the English curriculum is increasingly becoming national which is in tune with the postcolonial fighting phase outlined by Franz Fanon. It argues, with illustrations, that ELT with native cultural content would make English more acceptable to the Indian psyche and promote a changed vista of aesthetic-semantic nature and texture of language against the background of native experience and imagination.